EFFECT OF FORCED EXERCISE (TAP STRESS) ON DROSOPHILA MELANOGASTER AND EFFICACY OF ABHRAK BHASMA AS DIETARY SUPPLEMENT. - Subedi, Rambhadur P; Vartak, Rekha R; Kale, Purushottam G (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Generation of reactive oxygen species and other oxidants as an outcome of aerobic respiration has been well documented. During boosted muscular activities/exercise, there is an increase in the rate of respiration and subsequent generation of oxidants; for which, organisms possess various defense systems. There is, however, paucity of reports on the effect of forced exercise in Drosophila melanogaster. Methods: The present investigation reports a method for inducing forced exercise, the tap stress,â€ in D. melanogaster. This method takes advantage of the natural tendency of Drosophila flies to climb/fly upward in a cylindrical tube. Simplicity of assembly, ease of experimentation and cost effectiveness are some of the key advantages of this method. Tap stress has been assumed to manifest through the generation of oxidative stress, thus, parameters indicative of oxidative stress have been evaluated. Results: The results indicate that tap stress induces oxidative stress mainly by influencing the non-catalytic components; total reduced glutathione (GSH), GSH: oxidized glutathione ratio, and free radical scavenging capacity. The catalytic components (superoxide dismutase, and catalase), on the contrary, remain largely unaffected. Abhrak bhasma (AB) influences total GSH content with an increase by about 38Â±21%, while flies on control diet register a decrease in total GSH content by 34Â±7% during tap stress. Feeding flies on AB, specifically, show a prominent increase in the transcription levels of cap nâ€ collar C, heat shock protein 70 and catalase genes (>1.5 fold). Conclusion: Overall, dietary supplement of AB and ascorbic acid benefits Drosophila flies in the management of oxidative stress induced through tap stress. Â